Prevalence of postpartum depression in patients with migraine - Reis, Ana Clara Sfredo dos Santos e; Gonçalves, Ana Luiza Rodegheri; Santos, Bruna Oliveira Rodrigues dos; Silva, Júlia Milan Procópio e; Câmara, Lorenza de Ávila Gomes Carneiro Dutra; Jurno , Mauro Eduardo (Headache Medicine, 2022)
IntroductionMigraine is a frequent and chronic condition that affects 3 times more women than men. Overall, it shows that migraine is influenced by variables such as fluctuating hormones levels throughout life with migraine. Women can also experience symptoms of postpartum depression (PPD) which can cause issues for new moms in terms of behavior, emotion and cognition. Clinical investigations have shown that headaches affects pregnants and parturients.ObjectiveTo verify PPD in migraine and non-migrainous parturients.MethodsData was collected from a sample of 155 women over 18 years old in the obstetric center of Santa Casa de Misericórdia de Barbacena, from October 2021 to August 2022, in the first 24 hours after labor. Parturients who did not agree to participate and those with cognitive impairment were excluded. All patients signed an informed consent form and answered the Edinburgh Postnatal Depression Scale (EPDS) and the ID-MigraineTM, in addition to clinic data and concomitant disorders from the patient's record.Results25 of the 155 postpartum women achieved the criteria for migraine and 130 for non-migraine. Of the patients with postpartum depression associated with migraine, 4 were classified as migraine and 8 as non-migrainous. Among patients who had headaches during pregnancy, 11 had PPD compared to those who did not have headaches during pregnancy: 1. The OR=8.9 (CI 1.12-70) and RR=7.9 (CI 1.05-60) were higher compared to those who did not have PPD. The analysis did not find a relation between migraine and PPD. However, a relation was found between headaches during pregnancy and the presence of PPD (p